Karakteristik Struktur Dan Fungsional Aspal Komposit dengan Perbandingan 85%:15% - Samuel Nugroho Putra; Simon Sembiring; Agus Riyanto (Journal of Energy, Material, and Instrumentation Technology, 2021)
Synthesis and characterization of rice husk and asphalt silica composites was carried out with a ratio of 85%: 15%. Silica synthesis from rice husk was carried out by the sol-gel method. The materials used in this study were rice husks, asphalt, distilled water, gasoline, NaOH and HNO3. Then the silica and asphalt according to the comparison is set at 110oC. This study aims to look at the structural characteristics, functionality and physical properties, namely water content and thickness development of the sample. Based on the research that has been done, it can be concluded that from the results of XRD characterization the samples have silica and amorphous carbon structures, then based on FTIR characterization shows the -OH (hydroxil) functional groups occur at wave number 3524 cm-1, the hydroxide metal Si-OH (silanol) is oxidized into Si - O - Si and Si - O are formed at wave numbers 1084 cm-1, 810 cm-1 and 462 cm-1 and the formation of the C-H and C=O function group occurs at wave numbers 2923 cm-1 and 2361 cm-1. Then test the physical properties of the water content of 7.642% with a change in thickness development of 4.783%.